Fruit Fly, Anastrepha edentata Stone (Insecta: Diptera: Tephritidae) - Howard V. Weems (EDIS)
Anastrepha edentata Stone has been collected in the Florida Keys in every month of the year, but its host plants still are unknown. It is one of six species of fruit flies of the genus Anastrepha, which occur in Florida or which have been established in Florida at some time. According to Division of Plant Industry records, it has not been found in Florida since 1936. There is a possibility that this species has not survived in Florida. It is not considered to be of economic importance anywhere within its range. This revised 2-page fact sheet was written by H. V. Weems, Jr. and published by the UF Department of Entomology and Nematology, March 2012.